2016
DOI: 10.1111/vco.12206
|View full text |Cite
|
Sign up to set email alerts
|

High COX‐2 expression is associated with increased angiogenesis, proliferation and tumoural inflammatory infiltrate in canine malignant mammary tumours: a multivariate survival study

Abstract: COX-2 expression affects mammary tumourigenesis by promoting angiogenesis and cell proliferation, encouraging metastatic spread and tumour-associated inflammation. Samples of canine mammary tumours (n = 109) were submitted to immunohistochemistry to detect COX-2, CD31, VEGF, Ki-67, CD3 and MAC387 expression. Concurrent high expression of COX-2/CD31, COX-2/VEGF, COX-2/Ki-67, COX-2/CD3 and COX-2/MAC was associated with elevated grade of malignancy, presence of intravascular emboli and presence of lymph node meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 50 publications
3
45
0
4
Order By: Relevance
“…In the present study, firocoxib, a selective cyclo-oxygenase-2 (COX2) inhibitor, was chosen. Carvalho et al demonstrated an association between COX2 expression and aggressive biological behavior, including shorter survival, metastasis, and angiogenesis, emphasizing the usefulness of selective COX2 inhibitors in the treatment for canine mammary tumors (54).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, firocoxib, a selective cyclo-oxygenase-2 (COX2) inhibitor, was chosen. Carvalho et al demonstrated an association between COX2 expression and aggressive biological behavior, including shorter survival, metastasis, and angiogenesis, emphasizing the usefulness of selective COX2 inhibitors in the treatment for canine mammary tumors (54).…”
Section: Discussionmentioning
confidence: 99%
“…In canine mammary tumors there are only a limited number of studies focusing on the cross talk between COX-2, cancer cells, and immune cells [19, 73] and this topic is incompletely understood. Our team demonstrated a significant association of high COX-2 immunoexpression with CD3 + T-lymphocytes [19] and MAC387 macrophages [73].…”
Section: Inflammatory Cells and Cancer Cell Biomarkersmentioning
confidence: 99%
“…Our team demonstrated a significant association of high COX-2 immunoexpression with CD3 + T-lymphocytes [19] and MAC387 macrophages [73]. Tumors with concurrent high COX-2/CD3 and high COX-2/MAC were statistically associated with variables of tumor aggressiveness (high histological grade of malignancy, presence of neoplastic intravascular emboli, and presence of lymph node metastasis) and shorter overall survival of animals [73]. These findings suggest that, similarly to human breast cancer, T-lymphocytes, macrophages, and COX-2 share functions in canine mammary carcinogenesis.…”
Section: Inflammatory Cells and Cancer Cell Biomarkersmentioning
confidence: 99%
“…COX-2 expression has been associated with proliferation and angiogenesis in canine mammary tumours and mast cell tumours [16], but associations with these pathways have not been well established in canine melanocytic tumours.…”
Section: Introductionmentioning
confidence: 99%